Kompetensi Kepala Daerah dalam Penyelenggaraan Pemerintahan Daerah di Kabupaten Bone Provinsi Sulawesi Selatan Rentang Waktu 2013-2018 - Roslianah Roslianah; Tjahya Supriatna; Hyronimus Rowa; Rossy Lambelanova (Institut Pemerintahan Dalam Negeri (IPDN), 2020)
Huge authority that owned by local head should be supported by competency for optimizing local governance, beacuse several facts obligatory authority and optionary authority is not optimal beacuse local head is not understood his competency as a local leader in region. This research aims to 1) analyze local head competency of Bone regency in local governance; 2) arrange model of local head competency in local governance. This research is using governmental theory and Shermon's theory as an applied theory. This research also used qualitative approach which has 17 informants who derived from snowball sampling technique. Data gathering with documentation and interview as primary data. Data analyzing technique is using descriptive analysis which develop with triangulation technique. Research result shows that the leadership of Bone's head from 2013-2018 has fill the requirements. This result is derived from Shermon's competency theory analyzing, namely knowledge, skills, traits, social role, self image, and motive in realizing local givernance has been competent. New model that developing from local governance in Bone regency is local head managerial competency model.